Transcranial Magnetic Stimulation with the Maximum Voluntary Muscle Contraction Facilitates Motor Neuron Excitability and Muscle Force. (20th March 2012) - Touge, Tetsuo; Urai, Yoshiteru; Ikeda, Kazuyo; Kume, Kodai; Deguchi, Kazushi
Abstract : Three trials of transcranial magnetic stimulation (TMS) during the maximum voluntary muscle contraction (MVC) were repeated at 15-minute intervals for 1 hour to examine the effects on motor evoked potentials (MEPs) in the digital muscles and pinching muscle force before and after 4 high-intensity TMSs (test 1 condition) or sham TMS (test 2 condition) with MVC. Under the placebo condition, real TMS with MVC was administered only before and 1 hour after the sham TMS with MVC. Magnetic stimulation at the foramen magnum level (FMS) with MVC was performed by the same protocol as that for the test 2 condition. As a result, MEP sizes in the digital muscles significantly increased after TMS with MVC under test conditions compared with the placebo conditions (P < 0.05 ). Pinching muscle force was significantly larger 45 minutes and 1 hour after TMS with MVC under the test conditions than under the placebo condition (P < 0.05 ). FMS significantly decreased MEP amplitudes 60 minutes after the sham TMS with MVC (P < 0.005 ). The present results suggest that intermittently repeated TMS with MVC facilitates motor neuron excitabilities and muscle force. However, further studies are needed to confirm the effects of TMS with MVC and its mechanism.